Cytokine Profile in Patients with Glomerulonephritis Depending on the Clinical Course (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance. In recent years, convincing data have been obtained proving the link between the development of GN and "immune dysregulation", primarily concerning T-lymphocytes. Experiments have shown the damaging effect on glomeruli of a cell-mediated mechanism (Th1-type) of an adaptive immune response associated with the activity of IFN-γ.Thus, it seems that cytokines play an important role in the pathogenesis of GN. However, only isolated studies are known on the study of pro- and anti-inflammatory cytokines circulating in the blood in patients with various forms of GN.The purpose of study. To study the features of the immunopathogenetic mechanisms of the effect of immune system mediators on the development of various clinical forms of glomerulonephritisResults and conclusions. According to the final values of cytokine levels, it should be noted that in patients with nephrotic GN, the minimum values of IL-1β, RAYL-1β and IL-8 levels detected at the beginning of treatment remained. In patients with nephrotic form, only the level of IL-10 remained high for a long time, the average value of which, as at the beginning of treatment, had a minimal value relative to the indicators of other groups of patients. In addition, with nephrotic GN, the lowest values of IFN-γ were recorded at the end of treatment. The cytokine profile of patients with hypertension at the end of treatment combined with that of patients with nephrotic GN with a reduced value of IL-8 relative to other groups of patients. With mixed GN, high values of IL-1β, IL-10, IFN-γ and IL-1β/RAYL-1β were found.